118k views
4 votes
Simplify the expression -6(10+9v)

User Mmushtaq
by
4.8k points

2 Answers

6 votes

hello!

===========================================================

In order to simplify this expression, we need to use the distributive property, which states:-


\bigstar{\underline{\boxed{\pmb{a(b+c)=ab+ac}}}\longleftarrow\sf{the~distributive~property}

Where:-


\maltese we distribute a by multiplying it times b and c

Now, let's use this property to simplify our expression:-


\longrightarrow\sf{-6(10+9v)}


\longrightarrow\sf{-60-54v}

==========================================================

note:-

Hope everything is clear; if you need any clarification/explanation, kindly let me know, and I'll comment and/or edit my answer :)

User Janx
by
4.6k points
3 votes

Answer:

-60 - 54v or -60 + (-54v)

Explanation:

If you choose to expand this equation to make it easier, you can write it out as (-6 × 10) + (-6 × 9v). With this, you can simplify this to -60 + (-54v).

User Alex Just Alex
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.